Media and the path to peace - Wolfsfeld, Gadi (Communication, society, and politics., 2004)
This book examines the role the news media plays in peace processes, arguing that it is often destructive. Wolfsfeld examines three major cases: the Oslo peace process between Israel and the Palestinians; the peace process between Israel and Jordan; and the process surrounding the Good Friday Agreement in Northern Ireland.